2013
DOI: 10.1021/ic302743s
|View full text |Cite
|
Sign up to set email alerts
|

New Complexes of Chromium(III) Containing Organic π-Radical Ligands: An Experimental and Density Functional Theory Study

Abstract: The electronic structures of a series of chromium complexes 1-7 have been experimentally investigated using a combination of X-ray crystallography, magneto- and electrochemistry, and Cr K-edge X-ray absorption and UV-vis spectroscopies. Reaction of the dimer [Cr(II)2(μ-CH3CO2)4](0) with 2,2'-bipyridine (bpy(0)) produced the complex [Cr(III)(bpy(0))(bpy(•))(CH3CO2)2](0) (S = 1) (1), but in the presence of isopropylamine ((i)PrNH2) [Cr(III)(bpy(•))((i)PrNH2)2(CH3CO2)2](0) (S = 1) (2) was obtained. Both 1 and 2 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 61 publications
7
45
0
Order By: Relevance
“…[a] See bond labeling scheme in Figure 6. [14] Similar linear correlations between ligand redox state and bond lengths have been documented by us [15,16,18] and others [19] for N,NЈ-coordinated (bpy) n and (tpy) n ligands. It has been shown that an experimental assignment of the ligand oxidation level in a given coordination compound can be made from high-resolution X-ray structures alone by using these correlations.…”
Section: Dft Calculationssupporting
confidence: 76%
See 1 more Smart Citation
“…[a] See bond labeling scheme in Figure 6. [14] Similar linear correlations between ligand redox state and bond lengths have been documented by us [15,16,18] and others [19] for N,NЈ-coordinated (bpy) n and (tpy) n ligands. It has been shown that an experimental assignment of the ligand oxidation level in a given coordination compound can be made from high-resolution X-ray structures alone by using these correlations.…”
Section: Dft Calculationssupporting
confidence: 76%
“…The molecular structure is tetrahedral (Θ ≈ 90°), which is presumably a consequence of the steric demands of the ligand methyl substituents. On the basis of the DFT calculations outlined below, the electronic structure of this species is best described as [ (in red) [14] and [Ni ) 1-π-radical anions [14,15] and suggest that at least one ligand π-radical is present in each complex. Indeed, the spectrum of [ …”
Section: Wwweurjicorg Full Papermentioning
confidence: 99%
“…We have previously assigned these bands in the near‐infrared region 700–1200 nm as d→π* transitions of N , N ′, N ″‐coordinated (pdi · ) 1– π radical anions and its corresponding dianions 1. Very similar features have been reported for the spectra of [Cr III (pdi · )(pdi 0 )] 2+ ( S = 1) in 4 (350–400, 500, 750, 900 nm)7 and [Mn II (pdi · )] 0 (400, 550, ca. 1000 nm) 10.…”
Section: Resultssupporting
confidence: 84%
“…Values are taken from ref 1a. for six [M II (pdi 0 ) 2 ] 2+ species (M = Mn, Fe, Co, Ni, Zn) and [Cr III (pdi) 2 ] 2+ from ref 7. and this work (complex 3 ) and [Cp 2 Zr IV (pdi 2– )] 0 ref 10…”
Section: Resultsmentioning
confidence: 99%
“…1 The ground state of these complexes can also have significant radical anion character on the pyridine ligands. 24 The strong bond between the oxidized metal and the reduced pyridine is important for enabling this transfer of electrons, because reduction of free pyridine is very difficult in the absence of a metal (−2.7 V vs. SCE). 5 We have been interested in showing the potential for the parent pyridine to accept charge, and exploring the ways in which the pyridine responds to this additional charge.…”
mentioning
confidence: 99%